Determinación de la exactitud y precisión del método de ortofenantrolina para la determinación de hierro en agua de pozo en la Parroquia El Cambio mediante espectroscopía ultra violeta visible - Ludeña Zerda, Nataly E. (2009)
The present investigation talks about to the determination of the precision and exactitude of the method of underground water iron quantification by means of the ortofenantrolin, this investigation was on approval made in the research laboratory of the Faculty of Chemical Sciences and the Health of the Technical University of Machala.